2022
DOI: 10.3389/fmed.2021.797223
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Vitreous Amyloidosis Caused by a TTR Lys55Asn Mutation With Intraoperative Suprachoroidal Hemorrhage

Abstract: We report a vitreous amyloidosis patient with white vitreous opacities (footplates) adhering to the posterior lens capsule. A positive Congo-red stain and transthyretin (TTR) Lys55Asn mutation confirmed the diagnosis of vitreous amyloidosis. Optical coherence tomography (OCT) revealed fern-like material adhering to the the posterior pole retinal surface in both eyes. Visual acuity significantly improved after the first vitrectomy, but vitreous opacities recurred 4 years later. The patient appeared to have aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The p.K55T and p.L75R mutations of TTR genes have also been reported in Chinese families ( Long et al, 2012 ). Recently, a Chinese study reported that the TTR p.K55N mutation presented with sensorimotor neuropathy and severe autonomic dysfunction four years after the first diagnosis of ocular amyloidosis ( Xu et al, 2021 ). Most patients with p. G103R have only been reported to have ocular symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The p.K55T and p.L75R mutations of TTR genes have also been reported in Chinese families ( Long et al, 2012 ). Recently, a Chinese study reported that the TTR p.K55N mutation presented with sensorimotor neuropathy and severe autonomic dysfunction four years after the first diagnosis of ocular amyloidosis ( Xu et al, 2021 ). Most patients with p. G103R have only been reported to have ocular symptoms.…”
Section: Discussionmentioning
confidence: 99%